2021
DOI: 10.1111/ced.14722
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and disease burden in prurigo nodularis

Abstract: Summary Background Prurigo nodularis (PN) is a chronic inflammatory skin disease characterized by intense pruritus, but information on patient experience and impact on quality of life (QoL) remains understudied. Aim To characterize disease characteristics and QoL in a global sample of patients with PN. Methods An anonymous survey was distributed via patient support groups for PN. Results In total, 231 members responded to the survey. The majority of respondents reported itch localized both to nodules and to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 43 publications
2
33
0
2
Order By: Relevance
“…The depressed mood associated with PN may trigger self‐medication with stimulants, as stimulants are shown to increase dopaminergic and serotonergic signalling systems in the brain 7 . Additionally, pain is commonly reported by patients with PN, 8 which may help explain the increased risk of opioid use disorder identified here. An association between PN and cannabis use disorder also has not been demonstrated previously.…”
Section: Pn Vs General Population Pn Vs Ada Pn (N = 3345) General Pop...mentioning
confidence: 87%
“…The depressed mood associated with PN may trigger self‐medication with stimulants, as stimulants are shown to increase dopaminergic and serotonergic signalling systems in the brain 7 . Additionally, pain is commonly reported by patients with PN, 8 which may help explain the increased risk of opioid use disorder identified here. An association between PN and cannabis use disorder also has not been demonstrated previously.…”
Section: Pn Vs General Population Pn Vs Ada Pn (N = 3345) General Pop...mentioning
confidence: 87%
“…TrkA expression was significantly enhanced by IL-4 and IL-13 in vitro study of normal human epidermal keratinocytes (NHEK) and overexpression of TrkA can further enhance the proliferation of NHEK, suggesting the interplay between Th2 cytokines and keratinocytes through neuroinflammatory mediator [ 74 ]. Furthermore, NGF can sensitize and modulate the peripheral nerves [ 76 ], which might contribute to the hypersensitivity to sensory perception [ 77 ], the common symptom found in AD [ 78 , 79 ] and CNPG [ 7 ].…”
Section: Neuroinflammationmentioning
confidence: 99%
“…A European cross sectional-study revealed that 406 out of 509 patients with CNPG experienced moderate to severe itch intensity scores [ 6 ]. In addition to high intensity of itch severity, the pruritus in CNPG is often persistent and associated with burning, stinging, and pain [ 6 , 7 ]. Meanwhile, the lesions have a negative impact on their appearance, daily activities, and quality of sleep [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is more common among African Americans, with the highest prevalence among the elderly and a mean age between 51 and 65 years [10]. There is an increased prevalence of dermatological, psychiatric, and systemic comorbidities among CNPG patients; thus, CNPG can occur as a comorbidity to existing disease [7, 11, 12]. Particularly, atopic predisposition is a major prompting factor seen among approximately 50% of CNPG patients [2].…”
Section: Introductionmentioning
confidence: 99%